Circadian and seasonal variation in onset of acute myocardial infarction. Issue 28 (15th July 2022) - Xin, Minglong; Zhang, Shengming; Zhao, Longguo; Jin, Xiongjie; Kim, Weon; Cheng, Xian Wu
Abstract : The aim was to investigate the circadian and seasonal variation of acute myocardial infarction (AMI). Clinical data of 3867 AMI patients hospitalized from November 2010 to October 2019 in the Border Yanbian Minority Autonomous Prefecture, China were collected, and 3158 patients with definite AMI onset times were analyzed. The clinical data analyzed included the time of onset, nationality, age, laboratory data. We divided the patients into 4 groups based on the timepoint of their AMI onsets: 00:00–05:59, 06:00–11:59, 12:00–17:59, and 18:00–23:59. We also divided the patients based on nationality: Chinese Korean and Han groups. We observed that there is a circadian rhythm in the incidence of AMI, and the peak of AMI is in the morning (7:00–9:00). Unexpectedly, the incidence of AMI was significantly lower in the cold winter than that of other 3 warm seasons ( P < 0.01) and the peak of AMI presented at the months of the large contrast between day and night temperature difference (over 20°C) like May of Spring and October of Fall. Finally, there was no difference in circadian rhythm between Chinese Korean and Han, although these groups differed in age, body mass index, and the inflammatory cell level. These findings have shown a different seasonal and circadian variation in onset of AMI. Further studies are required to determine the pathophysiological mechanism(s) underlying these differences and to guide prevention of AMI for reducing its mortality and disability.